Adenovirus 2 early region 1A stimulates expression of both viral and cellular genes. - Svensson, C (1984)
The ability of products from the adenovirus early region 1A to stimulate viral and cellular gene expression has been studied, using a transient expression assay in HeLa cells. We show that the E1A 13S mRNA encodes a diffusible product which is capable of stimulating transcription of adenovirus genes as well as the rabbit beta-globin gene. The E1A 12S mRNA has no detectable stimulatory effect on either cellular or viral genes. Although being able to stimulate both types of genes, we find that the E1A regulatory protein enhances viral gene expression approximately 10 times more than beta-globin gene expression. We also find that when connected to the cis-acting SV40 enhancer element, the beta-globin gene cannot be further stimulated by the trans-acting E1A product. Finally, we find that transfection of either adenovirus or the beta-globin gene into 293 cells, which constitutively expresses the E1A gene products, leads to an enhanced expression which is 10- to 20-fold higher than obtained by co-transfection of HeLa cells. The 293 cells thus provide a simple assay to demonstrate E1A-mediated transcriptional regulation.